Prediction of Crack Propagation Directions in Dissimilar Metal-Welded Joints Using Phase-Field Models and Discussion of Its Mechanisms - Lingyan Zhao; Bin Yang; Zheng Wang (Science and Technology of Nuclear Installations)
Stress corrosion cracking (SCC) in dissimilar metal-welded joints (DMWJs) poses a significant threat to the safe operation of nuclear power plants. This study employs the phase-field method to analyze crack propagation paths at various positions in DMWJs of nuclear power safety ends. A user-defined material (UMAT) subroutine was implemented to characterize the mechanical heterogeneity of the heat-affected zone (HAZ) and fusion zone (FZ). The effects of Young’s modulus (E), critical energy release rate (GC), and mechanical heterogeneity on crack propagation paths were investigated. Results indicate that E has minimal impact on crack propagation paths, while GC significantly influences them. Mechanical heterogeneity in local regions, particularly in the HAZ and FZ, substantially affects crack propagation paths, with the HAZ having the most pronounced effect. Interface crack propagation is identified as the most hazardous. Notably, cracks in 316L/52Mw are less affected by mechanical heterogeneity compared to those in SA508/52Mb.